Using scripts and stories: illustrating the influences on drama performance assessment. Issue 1 (2nd January 2016) - Jacobs, Rachael
Abstract: The dramatic arts utilise emotion, introspection, artistry and interpretation from multiple perspectives to promote dialogue and reflection. Drama research can access these kinds of engagements by using artistic mediums to present phenomena, experiences and findings. This paper resulted from a research project investigating drama performance assessment in Australian schools. Data was collected in Year 11 and 12 Drama classes at six school sites, using ethnographical observation of performances, narrative and semi-structured interviews, and participant observation. Findings of the research indicate that there are several influences on students' performative responses for assessment, including the local curriculum and assessment practices, school and class cultures and the approach of the teacher. These influences are illustrated using mediums that complement the field of drama, specifically scripts and stories. This paper presents three of these artefacts; one collection of storied descriptions and two scripts, discussing the methodology used to create them and exploring future directions for the presentation of findings, using other mediums that complement the field of drama.